Efficient One-Pot Synthesis of 1, 4-Dihydropyridine and Polyhydroquinoline Derivatives Using Sulfanilic Acid-Functionalized Boehmite Nano-Particles as an Organic-Inorganic Hybrid Catalyst. (9th August 2022) - Khodabakhshi, Mohammad Reza; Kiamehr, Mostafa; Karimian, Ramin
Abstract: Boehmite nanoparticles (BNPs) with a wide surface area and a large number of surface hydroxyl groups were covalently functionalized by 3-chloropropyl trimethoxysilane to support sulfanilic acid. This is a hybrid catalyst was then characterized by Fourier transform infrared spectroscopy, field emission scanning electron microscopy (FESEM), thermal gravimetric analysis, X-ray diffraction and energy-dispersive X-ray spectroscopy. Accordingly BNPs@Si(CH2 )3 @NHSO3 H was used as an effective catalyst for the one-pot three-component Hantzsch condensation reaction of aryl aldehydes, ammonium acetate and ethylacetoacetate for synthesize polyhydroquinolines and 1, 4-dihydropyridine derivatives. These reactions were carried out in ethanol solvent under reflux conditions. This way offered here is operationally easy, environmentally benign, straightforward work-up, short reaction time and has high yield. Further, the heterogeneous catalyst be recycle simply and reused.